Series: Practical guidance to qualitative research. Part 7: Qualitative evidence synthesis for emerging themes in primary care research: Scoping review, meta-ethnography and rapid realist review - Albine Moser; Irene Korstjens (European Journal of General Practice, 2023)
AbstractThis article, the seventh in a series aiming to provide practical guidance for qualitative research in primary care, introduces qualitative synthesis research for addressing health themes in primary care research. Qualitative synthesis combines rigorous processes and authorial judgement to present the collective meaning of research outputs; the findings of qualitative studies – and sometimes mixed-methods and quantitative research – are pooled. We describe three exemplary designs: the scoping review, the meta-ethnography and the rapid realist review. Scoping reviews aim to provide an overview of the evidence/knowledge or to answer questions regarding the nature and diversity of the evidence/knowledge available. Meta-ethnographies intend to systematically compare data from primary qualitative studies to identify and develop new overarching concepts, theories, and models. Rapid realist reviews aim to provide a knowledge synthesis by looking at complex questions while responding to time-sensitive and emerging issues. It addresses the question, ‘what works, for whom, in what circumstances, and how?’We discuss these three designs’ context, what, why, when and how. We provide examples of published studies and sources for further reading, including manuals and guidelines for conducting and reporting these studies. Finally, we discuss attention points for the research team concerning the involvement of necessary experts and stakeholders and choices to be made during the research process.